Hydrothermal Synthesis and Characterization of Sodalite from Feldspar Mesawa Minerals - Amin, Ida Ifdaliah; Wahab, Abdul Wahid; Taba, Paulina; Mukti, Rino R.; S, Giovanno Alvin; Musa, Bulkis; Azis, Hijrah A. (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2025)
The mineral feldspar is a potential raw material in zeolite synthesis because of the high content of SiO2 and Al2O3. Characterization of X-ray diffraction (XRD) and X-ray fluorescence (XRF) on Mesawa feldspar minerals showed high crystallinity and aluminosilicate composition. The synthesis process uses the hydrothermal method with various times and concentrations of NaOH. The sample was mixed with NaOH, stirred until homogeneous at 300 rpm for 1 hour, and transferred to an autoclave. The autoclave was tightly closed and heated in an oven at 170 °C for 72 hours. XRD and XRF analysis revealed that the feldspar mineral had changed to sodalite with a purity of 90.89% and 90.06%; with a yield of 80.89% and 87.36%. FTIR characteristics show a specific peak for sodalite at 422-460 cm-1 related to Si-O bond vibrations, and absorption bands at 698 and 719 cm-1 related to Al-OH vibrations. The SEM results confirmed the morphology of the sodalite resembling balls like raspberries